OPTIMIZING THE USE OF ARTIFICIAL INTELLIGENCE IN INCREASING PUBLIC PARTICIPATION IN DIGITAL SERVICES - Eko Prasetyo; Fitria Firdiyani; Muhammad Hilman (DIA: Jurnal Administrasi Publik, 2025)
The development of digital governance has ushered in a new era of public administration, where the Tangerang City Government has implemented the Tangerang Live platform to provide online public services. The Tangerang Live application not only changes the way the government provides services, but also the way citizens participate. This research aims to explore the potential use of artificial intelligence in increasing digital public participation. The method used is a qualitative method by mapping public service platforms based on digital public participation features, as well as identifying the potential and opportunities for the use of AI in encouraging digital public participation. Data was collected through interviews and focus group discussions with informants from the Tangerang City Government which included the Communication and Information Service, the Manpower Office, the Population and Civil Registration Office, and the health Office. Documentation studies are also carried out to strengthen the foundation in the analysis process. The results of the study show that the level of public participation provided in the Tangerang Live application is at the consultation level. Optimization of the use of AI to increase public participation in online services can be designed by opening up participation spaces from various channels, which are then supported by the application of AI. The application of AI should be able to answer the challenge of implementing a digital platform that is able to function as digital information, digital consultation, and digital decision making